SUMOylation Connects Cell Stress Responses and Inflammatory Control: Lessons From the Gut as a Model Organ - Karhausen, Jörn; Ulloa, Luis; Yang, Wei (Frontiers in Immunology, 2021)
Conjugation with the small ubiquitin-like modifier (SUMO) constitutes a key post-translational modification regulating the stability, activity, and subcellular localization of its target proteins. However, the vast numbers of identified SUMO substrates obscure a clear view on the function of SUMOylation in health and disease. This article presents a comprehensive review on the physiological relevance of SUMOylation by discussing how global SUMOylation levels—rather than specific protein SUMOylation—shapes the immune response. In particular, we highlight the growing body of work on SUMOylation in intestinal pathologies, because of the unique metabolic, infectious, and inflammatory challenges of this organ. Recent studies show that global SUMOylation can help restrain detrimental inflammation while maintaining immune defenses and tissue integrity. These results warrant further efforts to develop new therapeutic tools and strategies to control SUMOylation in infectious and inflammatory disorders.